The evolution of natural law understanding in the context of political and legal thought (Journal of actual problems of jurisprudence, 2018)
The interpretation of natural law in the Kazakhstani legal thought is characterized by ambiguous approaches of two basic trends of legal science. The essence of the conflict refers to the nature of the natural law and its relation to reality. The question is whether the doctrine of natural law is considered to be purely a logical structure, ethical ideal of human beings or an expression of real human values, with the impartial nature. In the given article we have tried to analyze and give a brief historical and legal back observation of natural law concept evolution in the global political and legal thought.Key words: State, spirit, agreement, natural law, freedom, people, philosophy, human.